A model United Nations experiment on climate negotiations - Elisa Hofmann; Lucas Kyriacou; Klaus M. Schmidt (Journal of Economics and Statistics, 2023)
Weitzman, M.L. (2014. Can negotiating a uniform carbon price help to internalize the global warming externality? J. Assoc. Environ. Resour. Econ. 1: 29-49) proposed that focusing international climate negotiations on a uniform common commitment (such as a uniform carbon price) is more effective than negotiations on individual commitments (as in the Paris agreement) in achieving ambitious climate action. We put this hypothesis to an experimental test by simulating international negotiations on climate change in collaboration with Model United Nations associations. This novel experimental format combines some of the advantages of lab and field experiments. Our results offer support for Weitzman's hypothesis and indicate that negotiating a common commitment on a uniform carbon price may yield higher emission reductions in the long run and more participation than individual commitments à la Paris.
Keywords: C81; C93; F51; H87; Q54; 330; climate negotiations; model united nations; negotiation design; uniform carbon price